Wayang Kulit Bali Sebagai Media Komunikasi - Ida Bagus Wika Krishna; Ida Bagus Putu Eka Suadnyana (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2020)
Communication of traditional wayang kulit performance art as one of the communication media that still has a place of honor and is favored by the majority of Balinese Hindus. The main function of the Balinese shadow puppet show is a dish that is enjoyed as a spectacle, but the shadow puppet show is sometimes coupled with certain ceremonies. Due to the existence of public trust in the sacred value of shadow puppets and can also be integrated with ceremonies that are held, complementary, or only accompanying. The ceremony is intended to glorify the ancestors, expressing gratitude and relating to a request is an important event that is considered sacred and needs to be completed or accompanied by performing arts at the time of its implementation. The Balinese shadow puppet show is presented in one form of story in the play so that the shadow puppet show contains a lot of value in it. The Balinese wayang kulit performance as a classic communication medium that presents various functions such as conveying information, teaching, and moral education does not only use classical or traditional values. Puppet shows also present universal values ​​such as depictions of human life, good behavior that must be chosen by humans.